The kinds of home health care and the practice of health professionals - exploratory and descriptive research - Kriscie K. Venturi; Maria R Lacerda; Samantha R Oliniski; Clélia M Giacomozzi; Thiago C Truppel (Online Brazilian Journal of Nursing, 2007)
The domiciliary assistance to the health holds four categories: domiciliares attention, attendance, visit and internment; witch must be understood between the professionals of the area. Thus, this quail-quantitative research was become fulfilled objectifying: to verify if the professionals of the health they understand and they distinguish the main concepts from the domiciliary attention to the health; e to understand as the use of these concepts for the same ones is related with its practical professionals. The data had been collected of 219 professionals of health for a composed instrument for referring closed questions to the concepts of categories in study. It was evidenced existence of a difficulty of these professionals in discerning the categories from the domiciliary attention to the health, as well as in relating them it the pratical professional, of form to adjust the used term what it is carried through. Still, this if finds disarticulated and dispossessed of the context of the domiciliary attention to the health. Thus, we detach the necessity of qualification of these citizens for a full professional performance of health.